Video Project to Enhance Comprehension of TOEIC Material - Eva Fachriyah; Ratu Dea Mada Badriyah (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2023)
This study aims to investigate the application of video project to comprehend TOEIC materials in the "TOEIC preparation" course. The research method used is mix method, which is descriptive qualitative and quantitative research. During one semester, students are given the task of creating video content that re-explains each material that has been explained by the lecturer in the class. Data was collected through observation, interviews, questionnaires to gain an in-depth comprehension of students' experiences and perceptions regarding the assignment of video projects, and pre-test and post-test to know the enhancing of comprehension. The score’s TOEIC of pre-test and post-test were analyzed using the T-test. The research findings show that the assignment of video projects has a positive impact on students' comprehension of the TOEIC preparation material. Through the process of making videos, students are actively involved in re-interpreting and conveying information in a structured manner. Students' English speaking ability also experienced a significant increase. In producing video content, they practice speaking English by expressing ideas and explaining material verbally. In addition, the assignment of video projects also increases student motivation and involvement in learning. This creative activity provides an interesting and interactive way to study TOEIC preparation material, thereby increasing their interest and participation in the learning process. The videos produced by students can also be an additional learning resource for other students in comprehension the TOEIC preparation material. This study concludes that the use of video project is effective in increasing comprehension of the material in the TOEIC preparation course. The result questionnaire revealed that 60% strongly agree and 30% agree. The implication of this research is the importance of adopting active, creative and collaborative learning strategies in an effort to improve the quality of learning English. Based on the quantitative result using T test analysis, it could be said that video project could enhance TOEIC comprehension.